Comparison of Tests for Fetal Liver Cells Viability after Cryopreservation - Skorobogatova, N. G. (Problems of Cryobiology and Cryomedicine, 2006)
There was carried out a comparative analysis of the results on the estimation of viability for freshly isolated and cryopreserved human fetal liver (HFL) cells using non-specific tests: vital staining of cells with trypane blue, ethydium bromide (EB), fluorescein diacetate (FDA) hydrolysis to fluorescein; ability of cell to adhesion. The performed tests reflect various aspects of cell viability. Staining with trypane blue and EB produced the similar results. FDA-test does not reveal a real number of viable HFL cells. The fraction of cells resistant to vital dyes, where no fluoresceine was found, was revealed by the combination of three methods of viability assessment. The non-specific adhesion test allows to estimate the integrity of HFL cells of adhesive pool. Simultaneously with keeping the number of adhesive HFL cells after cryopreservation there were found the morphological differences of cells, being adhered to the plastic, comparing to the native control. Combined usage of stated tests allows to provide the more complete primary characteristics of heterogenous suspensions of non-differentiated cells, in particular, HFL ones.